2023
DOI: 10.1007/s11831-023-09930-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Research Trends in Africa: A 30 Years Overview with Bibliometric Analysis Review

Abstract: The machine learning (ML) paradigm has gained much popularity today. Its algorithmic models are employed in every field, such as natural language processing, pattern recognition, object detection, image recognition, earth observation and many other research areas. In fact, machine learning technologies and their inevitable impact suffice in many technological transformation agendas currently being propagated by many nations, for which the already yielded benefits are outstanding. From a regional perspective, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 160 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…The VOSviewer tool was used to visualize networks of authors, countries, journals, and keywords. Similarly, the bibliometric analysis conducted by Ezugwu et al (2023) identified the main research areas related to machine learning, such as its practical applications and economic impact. Sökmen et al (2023) also conducted a bibliometric analysis, in their case, on self-regulated learning in primary education.…”
Section: Discussionmentioning
confidence: 99%
“…The VOSviewer tool was used to visualize networks of authors, countries, journals, and keywords. Similarly, the bibliometric analysis conducted by Ezugwu et al (2023) identified the main research areas related to machine learning, such as its practical applications and economic impact. Sökmen et al (2023) also conducted a bibliometric analysis, in their case, on self-regulated learning in primary education.…”
Section: Discussionmentioning
confidence: 99%